Gender Equality in the Welding Industry - Hairuddin, Syaidatul Nadia; Lai Chee Sern (Journal of TVET and Technology Review, 2025)
Gender equality is a key component of sustainable national development, particularly in the welding industry where gender disparities remain prominent. The welding industry is one such sector in which women continue to be underrepresented despite growing awareness and policy efforts aimed at encouraging their involvement. This paper explores gender equality in the welding industry by examining trends, challenges, and structural factors that influence women’s participation. Although Malaysia has introduced various policies, educational initiatives, and workforce strategies to promote gender equity, women’s involvement in welding remains low due to persistent cultural norms, stereotypes, and societal perceptions that associate welding with heavy physical work and male dominance. Technological advancements such as automation and improved safety measures have reduced the physical demands of welding and created more opportunities for women; however, systemic barriers continue to restrict their progress. These barriers include unequal access to hands-on training, limited exposure to technical tasks, a shortage of female mentors, and subtle forms of workplace discrimination that affect confidence, motivation, and career advancement. Gender equality in welding is essential not only for social fairness but also for increasing the nation’s talent pool, strengthening industry competitiveness, and supporting broader economic goals. Greater female participation can enhance workforce diversity, stimulate innovation, and contribute to Malaysia’s commitments to the Sustainable Development Goals (SDGs), particularly those related to quality education, decent work, and reduced inequalities. This paper highlights the need for integrated approaches—combining educational reforms, supportive institutional policies, workplace inclusivity, and societal awareness—to create equitable opportunities for all individuals and build a more resilient, future-ready technical workforce.